Upaya Pengembangan Perilaku Hidup Bersih Dan Sehat (PHBS) Pada Kalangan Anak-Anak Desa Buter Balik - Agung Rida Ilahi; Cut Julita; Lili Rahmayanti; Fatimah Fatimah; Sofi Imamah Banurea; Mahmud Basuki (Pusat Riset dan Inovasi Nasional, 2023)
Buter Balik Village is a village in Kute Panang District, Central Aceh District, Aceh Province. Rural areas located in mountainous areas far from urban areas. The method used in this article is the center and around (SELING) and outreach. The purpose of this socialization is to teach Clean and Healthy Behavior (PHBS) to the children of Buter Balik Village. The results of this activity were that the children enthusiastically took part in the PHBS understanding agenda, there were three variables of PHBS knowledge for the children of Buter Balik Village, namely maintaining cleanliness, neat nails, and using clean water, but knowledge about clean and healthy living in the environment around the children Buter Balik Village still needs to be improved, Buter Balik Village has the majority of livelihoods as farmers so parents are busy or don't spend enough time with their children which results in children not understanding knowledge about clean and healthy living behaviors. To prevent the occurrence of PHBS problems in children by implementing lifestyle behaviors such as maintaining healthy, nutritious food intake, namely 4 healthy 5 perfect and also doing routine morning activities such as exercising.